DETERMINANTS OF GREEN COSMETIC PURCHASE BEHAVIOUR AMONG YOUNG ADULTS IN MALAYSIA: A CONCEPTUAL PAPER - Sakri, Siti Khatijah Mohamad; Yasin, Nurul Hafizah Mohd; Ab Rashid, Ahmad Faezi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Green cosmetic purchase behaviour among young adults in Malaysia represents a vital aspect of sustainable consumption within the expanding beauty and personal care sector. Despite growing awareness and positive attitudes toward natural and organic cosmetics, empirical evidence reveals a persistent intention-behaviour gap, where actual purchases of green cosmetics remain limited among this demographic. This conceptual paper addresses this gap by developing an extended Theory of Planned Behaviour (TPB) framework that integrates attitude toward green cosmetics, green self-identity, ethical concern (particularly regarding animal welfare), perceived consumer effectiveness, and social media influencer exposure as key determinants of green cosmetic purchase behaviour. The framework explicitly maps these constructs to TPB components: attitude as the core attitudinal factor, perceived consumer effectiveness to perceived behavioural control, social media influencer exposure as a digital form of subjective norm, and green self-identity with ethical concern as internal moral-identity extensions. By synthesising prior empirical studies from green consumption and cosmetics literature, the paper proposes five testable hypotheses suitable for validation through future cross-sectional surveys of Malaysian young adults. Theoretically, this study contributes by extending TPB through novel integration of moral-identity and digital influence factors in an underexplored Malaysian context. Practically, it offers actionable insights for marketers and policymakers to bridge the attitude-behaviour gap and promote sustainable cosmetic consumption patterns.